Organizational Climate and Job Anxiety of Primary School Teachers with Special Reference to Coimbatore District (International Journal of Scientific Research and Management (IJSRM), 2021)
The number of workloads borne by the teacher will result a negative impact. An organizational climate is crucial because it can generate a comfortable working condition for teachers. Otherwise, an unfavorable organizational climate can impact poor working conditions that affect teachers to experience job Anxiety. This study aimed to determine the effect of workload and organizational climate on the work Anxiety of primary school teachers in Coimbatore. In this study an attempts has been made to find out the relationship between organizational climate and job anxiety of primary school teachers. The sample consisted of 60 teachers selected randomly from various public and private primary schools. A set of tools containing organizational climate and job anxiety was used to gather information. The data were analyzed by t-test and person’s coefficient correlation. The results revealed that (43.3%) of the respondents are moderate level of organizational climate, (40%) of the respondents are good level of organizational climate and (16.7%) of the respondents are poor level of organizational climate and (43.3%) of the respondents are low level of job anxiety, (40%) of the respondents are moderate level of job anxiety and (17%) of the respondents are high level of job anxiety.